2020
DOI: 10.18621/eurj.483442
|View full text |Cite
|
Sign up to set email alerts
|

The additional diagnostic value of NLR and PLR for CA-125 in the differential diagnosis of endometrioma and benign ovarian cysts in women of reproductive age: a retrospective case-control study

Abstract: Objectives: Aim of this study is to investigate the diagnostic value of neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) for cancer antigen-125 (CA-125) in a differential diagnosis of endometrioma from benign ovarian cysts. Methods: In this retrospective study, the medical data of a total of 213 patients aged < 40 years who underwent laparoscopic or laparotomic surgery for ovarian cysts between April 2015 and June 2018 were analyzed. The patients were divided into two groups, as those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…NLR and MPV are increasingly used as indicators of cancer and various systemic diseases as well as systemic inflammation. Although there are studies on whether these parameters may have predictive value in cases such as preeclampsia, endometriosis, and tuba ovarian abscess in gynecology and obstetrics practice, there is no study on the value of these parameters in ICP (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…NLR and MPV are increasingly used as indicators of cancer and various systemic diseases as well as systemic inflammation. Although there are studies on whether these parameters may have predictive value in cases such as preeclampsia, endometriosis, and tuba ovarian abscess in gynecology and obstetrics practice, there is no study on the value of these parameters in ICP (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…A recent research conducted by Örgül et al ( 12 ) had shown that increased first-trimester WBC and neutrophil counts may be predictive of early-onset preeclampsia. Although studies have been conducted to determine whether these parameters may have predictive values in the cases such as endometrioma and tubo-ovarian abscess in gynecology and obstetrics practice, there is no study that aimed to determine the value of these parameters in IUGR ( 13 , 14 ) .…”
Section: Discussionmentioning
confidence: 99%